Symptoms of the risk of mobile phone addiction and symptoms of mobile phone addiction in Polish young people aged 13 to 24 years measured using Potembska and Pawłowska’s Mobile Phone Addiction Assessment Questionnair - Pawłowska, Beata; Potembska, Emilia (Current Problems of Psychiatry, 2012)
The aim of this study was to determine the prevalence of mobile phone addiction and of the risk of mobile phone addiction in young peo-ple aged 13–24 years on the basis of their scores on Potembska and Pawłowska’s Mobile Phone Addiction Assessment Questionnaire. Participants: The study was conducted in the years 2010–2011 and included a group of 694 young people aged 13 to 24 years. 206 of the participants (67 boys and 139 girls) attended a secondary school, 113 (48 boys and 65 girls) attended a gymnasium, and 375 were university students (123 men and 252 women). Methods: The study was conducted using a socio-demographic questionnaire and the Mobile Phone Addiction Assessment Questionnaire (KBUTK) by Potembska and Pawłowska. KBUTK consists of 33 items. The coefficients of reliability for the individual scales were high: Cronbach’s alpha=0.91 for the Acceptance and Closeness scale; Cronbach’s alpha=0.81 for Addiction to Mobile Phone Features; Cronbach’s alpha=0.85 for Addiction to Text Messaging and Voice Calls; and Cronbach’s alpha=0.83 for Indirect Communication. The reliability coefficient for the global KBUTK score was 0.91. A test-retest was performed within one month on a group of 65 persons and the following correlation coefficients were obtained for the individual scales: Acceptance and Closeness scale, rtt=0.79, (p<0.001); Addiction to the Mobile Phone Set, rtt=0.78, (p<0.001); Addiction to Text Messaging and Voice Calls, rtt=0.81, (p<0.001); and Indirect Communication rtt=0.74, (p<0.001). The correlation coefficient for the global scale was rtt=0.79; (p<0.001). Results: The participants had a mean score on the KBUTK of 28 points with a standard deviation of 19 points. The lowest score on the global KBUTK scale was 0 and the highest 121 points (out of a maximum possible score of 132 points). Persons whose score on the global KBUTK scale was within the range of 31 to 69 points (i.e. within the range from the mean score to plus two standard deviations from the mean) were considered to be at risk of mobile phone addiction, and those whose score was two or more deviations from the mean (70 points and above) were considered addicted. Out of the 694 participants, 2.9% met the criteria for mobile phone addiction (scored 70 or more points – more than 2 standard deviations from the mean), and 35.3% met the criteria for the risk of mobile phone addiction (scored 31 to 69 points – the area between the mean and two standard deviations above the mean). In the group of 456 women, 2.9% met the criteria for mobile phone addiction, as measured using the KBUTK Questionnaire, and 35.1% of the participants met the criteria for the risk of mobile phone addiction. In the group of 238 men, 2.5% were addicted and 30.3% met the criteria for the risk of mobile phone addiction. Conclusion: 1. More women than men meet the criteria for mobile phone addiction and the risk of mobile phone addiction. 2. In Poland the criteria of mobile phone addiction are fulfilled by circa 3% of young people (2.9% of women and 2.5% of men), whereas the risk of developing this addiction is fulfilled by 35% of individuals (35% of women and 30.3% of men).